Water deficit under continuous light enhances the thermal stability of photosystem II in Homalothecium lutescens moss - Dulai, Sándor (Acta Biologica Szegediensis, 2002)
The thermal stability of photosystem II was examined under different (light and water deficit) treatments in the moss H. lutescens. The decrease in water content under continuous light effected a heat-tolerance increase, further intensified by increasing excitation energy levels. The breakpoints (T, T, F1/2) of the F, vs. T curves significantly shifted towards higher temperatures even under a 30-minute moderate (-1.3 MPa) osmotic treatment, and this was partially inhibited by DTT. Both moderate and higher water deficit (-2.5 MPa) resulted in an increase in thermal stability, independent of the excitation energy level. This effect of water deficit remained observable over a fairly long period. Since in a dark-adapted state the critical values of the F0 vs. T curves did not shift towards significantly higher temperatures with an increase in water deficit, it seems likely that rapid thermal stability increase of PS II induced by water deficit occurs only in energized photosynthetic membranes.